HIV‐1 envelope trimer has similar binding characteristics for carbohydrate‐binding agents as monomeric gp120. Issue 7 (26th February 2013) - Hoorelbeke, Bart; van Montfort, Thijs; Xue, Jie; LiWang, Patricia J.; Tanaka, Haruo; Igarashi, Yasuhiro; Van Damme, Els J.M.; Sanders, Rogier W.; Balzarini, Jan
Abstract : gp120 binds to AH by surface plasmon resonance (View Interaction: 1, 2) Abstract : ► Similar binding kinetics of CBAs for monomeric gp120 and trimeric gp140. ► Similar binding kinetics of the Ab 2G12 and sCD4 for monomeric gp120 and trimeric gp140. ► Two‐ to threefold stronger affinity of Ab b12 and DC‐SIGN for trimeric gp140. ► SPR‐directed binding kinetics with monomeric gp120 are relevant for native gp140 trimer.